2014
DOI: 10.1128/cvi.00560-14
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Escalating Dosages of a Single Oral Administration of Peru-15 pCTB, a Candidate Live, Attenuated Vaccine against Enterotoxigenic Escherichia coli and Vibrio cholerae

Abstract: c Enterotoxigenic Escherichia coli (ETEC) organisms are a leading cause of infectious diarrhea in developing countries. A live, attenuated cholera strain that expresses high levels of the nontoxic B subunit of cholera toxin, which might also serve as an ETEC protective antigen, was evaluated for safety, excretion, and immunogenicity in healthy volunteers. We enrolled four inpatient dose-escalation cohorts of 15 to 16 eligible subjects to randomly (3:1) receive a single oral dose of vaccine or placebo (buffer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Furthermore, the vaccine was safe up to 1 × 10 10 CFU. 70 Recently, an oral recombinant adenovirus influenza vaccine induced significant increases in haemagglutination inhibition and high titers of microneutralization antibodies with only mild adverse effects. 71 Moreover, Euvichol is an inactivated bivalent oral cholera vaccine tested during a phase I clinical trial in healthy South Korean adult males that induced a seroconversion rate of 95% and 45% for Vibrio cholera O1 and O139, respectively.…”
Section: Clinical Trials For Oral Vaccinesmentioning
confidence: 99%
“…Furthermore, the vaccine was safe up to 1 × 10 10 CFU. 70 Recently, an oral recombinant adenovirus influenza vaccine induced significant increases in haemagglutination inhibition and high titers of microneutralization antibodies with only mild adverse effects. 71 Moreover, Euvichol is an inactivated bivalent oral cholera vaccine tested during a phase I clinical trial in healthy South Korean adult males that induced a seroconversion rate of 95% and 45% for Vibrio cholera O1 and O139, respectively.…”
Section: Clinical Trials For Oral Vaccinesmentioning
confidence: 99%
“…In contrast, the mice immunised with HaitiV elicited anti-CTB IgG (~30 ELISA units) and anti-CTB IgA (~300 ELISA units) on day 42 [55]. Distinctly, the mice immunised with Peru-15p CTB-a live-attenuated cholera vaccine-expressed high levels of CT-B (~30 fold) and recorded a high level of anti-CT-B titre with a geometric mean titre (GMT) of 3200 by day 42 [56].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, live OCVs appear to be more effective in children less than 5 years of age (9,10), a group that is highly susceptible to death from cholera and that is not adequately protected by killed OCVs. In volunteer studies, these vaccines have shown great promise (11,12), but none are approved for use in cholera endemic regions.…”
Section: Introductionmentioning
confidence: 99%